Effectiveness of neuromuscular electrical stimulation for reducing oedema: A systematic review - Louise C. Burgess; Tikki Immins; Ian Swain; Thomas W. Wainwright (Medical Journals Sweden, 2019)
Objective: This systematic review aimed to assess the clinical impact of neuromuscular electrical stimulation as a treatment modality for patients with oedema. Data sources and study selection: PubMed was searched up to July 2018 for randomized and non-randomized clinical trials comparing neuromuscular electrical stimulation vs no stimulation following the formation of oedema. A modified Downs and Black checklist was used to evaluate the quality of the evidence. Data synthesis: Initial searches yielded 150 results. Removal of duplicates reduced this number to 97 results. Seventy-five studies were excluded following a review of titles and abstracts. Full-text screening eliminated 15 studies. A final total of 7 studies met the inclusion criteria. Six studies supported the use of neuromuscular electrical stimulation for oedema reduction, and one study did not find an effect, but reported inter-group variance. Conclusion: The results of this systematic review support the use of neuromuscular electrical stimulation for ameliorating the abnormal accumulation of interstitial fluid, which is clinically shown as oedema. Neuromuscular electrical stimulation is effective in a number of rehabilitation settings and patient groups, for treatment of both upper and lower limb oedema. However, further trials are needed to reinforce these findings.